Investigation of a retrospective study of clavicle fractures in children (Eurasian Medical Research Periodical, 2022)
This paper aims to Investigation of a retrospective study of clavicle fractures in children. A retrospective study was conducted in different hospitals in Iraq. Investigation of a retrospective study of clavicle fractures in children, where 100 children were collected and distributed into 66 boys and 34 girls. An X-ray of the clavicle is one of the most common diagnostic techniques based on the use of X-rays. It allows to obtain data on the state of bone tissue, determine its fractures, visualize neoplasms, as well as congenital defects and skeletal anomalies. The statistical analysis program IBM SPSS SOFT 22 was relied upon for the purpose of analyzing the data and demographic information that were pulled from the hospital's electronic record, and the mean value SD to the patients' ages was 8.5 ± 1.8 And through the distribution of patient radiological follow-up follow-up fractures according to age, we note that the number of days increases with age, and this indicates a direct relationship with age We conclude from this study that it is possible for children to develop clavicle fractures and turn into complications. Despite the lack of experimental and scientific studies on this subject, some complications were found